RNA interference suppression of the receptor tyrosine kinase Torso gene impaired pupation and adult emergence in Leptinotarsa decemlineata. (December 2015) - Zhu, Tao-Tao; Meng, Qing-Wei; Guo, Wen-Chao; Li, Guo-Qing
Graphical abstract: Highlights: A receptor tyrosine kinase Torso gene was cloned in Leptinotarsa . RNAi of LdTorso impaired pupation and adult emergence. RNAi of LdTorso downregulated MAPK genes. JH and 20E titers were affected in the LdTorso RNAi larvae. JH and 20E pathways were disrupted in the LdTorso RNAi larvae. Abstract: In Drosophila melanogaster prothoracic gland (PG) cells, Torso mediates prothoracicotropic hormone (PTTH)-triggered mitogen activated protein kinase (MAPK) pathway (consisting of four core components Ras, Raf, MEK and ERK) to stimulate ecdysteroidogenesis. In this study, LdTorso, LdRas, LdRaf and LdERK were cloned in Leptinotarsa decemlineata . The four genes were highly or moderately expressed in the larval prothoracic glands. At the first- to third-instar stages, their expression levels were higher just before and right after the molt, and were lower in the mid instars. At the fourth-instar stage, their transcript levels were higher before prepupal stage. RNA interference-mediated knockdown of LdTorso delayed larval development, increased pupal weight, and impaired pupation and adult emergence. Moreover, knockdown of LdTorso decreased the mRNA levels of LdRas, LdRaf and LdERK, repressed the transcription of two ecdysteroidogenesis genes ( LdPHM and LdDIB ), lowered 20E titer, and downregulated the expression of several 20E-response genes ( LdEcR, LdUSP, LdHR3 and LdFTZ-F1 ). Furthermore, silencing of LdTorso induced the expression of a JH biosynthesis gene LdJHAMT, increased JH titer, and activated the transcription of a JH early-inducible gene LdKr-h1 . Thus, our results suggest that Torso transduces PTTH-triggered MAPK signal to regulate ecdysteroidogenesis in the PGs in a non-drosophiline insect.